Implementation of the Qur'an Reading and Writing Program to Increase Children's Interest in Reading the Qur'an During the Covid-19 Pandemic - Muhammad Ghazali; Disniarti Disniarti; Putri Hana Pebriana; Afif Alfiyanto; Fitri Hidayati (EduLine: Journal of Education and Learning Innovation, 2022)
This study aims to determine children's interest in the implementation of the RWA (Read-Write Al-Qur'an) program during the Covid-19 Pandemic at the Qur’anul Karim recitation center RT 09 Village 12 Ulu Palembang City. This study uses qualitative research with a descriptive approach which is research that seeks to describe the events and events that take place at the time of the study in accordance with what they are. Based on the results of the study it can be concluded from the RWA program using the Iqra method can increase the interest of students in reading the Qur'an and writing the letters of the Qur'an correctly and neatly. In addition, students can memorize a number of short letters, certain verses, and daily prayers. so they can read their prayers well and get used to living in an Islamic environment. Supporting factors in the implementation of the Qur'an Reading and Writing Program are 1) the policy of village administrators and community leaders in the 12 Ulu sub-district to allow researchers to use Balai as a place for program implementation; 2) The Al-Qur'anul Karim Study Center is equipped with three fans that cool the room so that teachers and children feel comfortable; 3) The Qur'an is available quite a lot; 4) A room that has several windows so that the lighting from the sun is perfect; 5) Availability of places to wash hands; 6) Cleaning tools such as brooms, shovels, buckets and so on are available to facilitate cleaning after using the Hall; and 7) Children who take part in the Al-Qur'an Reading and Writing Program often come on time. While the inhibiting factors are 1) fewer children are coming because children start the new school year by studying online at their respective homes. ; 2) some children are not fluent in reading the Qur'an or Iqra, and some have forgotten how to read the Qur'an or Iqra because they never repeat it at home; 3) When writing the letters that are exemplified, some of the children's writing is not neat, careless, irregular and sometimes wrong in writing.